CURRENT TRENDS IN MEDICAL EDUCATION - Aslam, Muhammad (Pakistan Journal of Physiology, 2009)
The undergraduate medical studies, postgraduate medical education, Continuing Medical Education (CME) and Continuous Professional Development (CPD) may be considered a continuum to make us â€˜lifelong learnersâ€™. There is a famous adage â€œseek knowledge from cradle to graveâ€ which substantiates this philosophy. The â€˜tomorrowâ€™s doctorâ€™ or a doctor in the new millennium doesnâ€™t have to be only knowledgeable in medical science but he or she needs to have a sound scientific foundation (knowledge), clinical (professional skills), professional values and attitudes and has a social responsibility of caring population health. Besides, he or she has to develop or learn critical thinking, managerial skills, advocacy, communication skills and collaboration. Obviously, this gigantic task cannot be carried out until and unless we (the medicos) are not well versed with the current trends of medical education and do not adapt the inferences of the recent developments in health sciences. It is a fact that role-models, faculty developers and resource availability stand amongst the major pre-requisites for implementing these current trends. And, to ensure sustainability of the programmes, cultural limits and regional needs may also be taken into an account. In brief, we the medicos may reveal openness of minds to study, accept, adopt and adapt the changing trends in medical education to become life long learners to mitigate the pains of the ailing community.